2021
DOI: 10.1080/14623943.2021.1913720
|View full text |Cite
|
Sign up to set email alerts
|

Finnish general upper secondary students’ metacognitive awareness in foreign language learning

Abstract: Our objective with this study was to investigate students' metacognitive awareness (MA) and its association with course grades in general upper secondary foreign languages, to foster reflective practices. A total of 267 foreign language students at Finnish schools answered an online survey, and the data were analysed quantitatively. Based on the results, the students' levels of MA were high in foreign languages, students at urban schools had higher levels than students at rural schools, and students with high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
0
5
0
1
Order By: Relevance
“…As to the amount of feedback, teachers might feel that boys need more feedback than girls because teachers find boys to be unmotivated and less attentive (Riley, 2014;Åhslund & Boström, 2018). Another explanation is that boys need more feedback as they generally receive lower grades compared to girls (Kupiainen et al, 2018;Tarnanen & Huhta, 2011), and boys' levels of metacognitive awareness are also lower compared to girls (Mäkipää et al, 2021b), which might suggest that boys are unable to use teacher feedback efficiently. Due to their lesser results and levels of metacognitive awareness, it is probable that boys' learning to learn skills are inferior to those of girls, which is why teachers provide boys with more feedback.…”
Section: Implications Of the Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As to the amount of feedback, teachers might feel that boys need more feedback than girls because teachers find boys to be unmotivated and less attentive (Riley, 2014;Åhslund & Boström, 2018). Another explanation is that boys need more feedback as they generally receive lower grades compared to girls (Kupiainen et al, 2018;Tarnanen & Huhta, 2011), and boys' levels of metacognitive awareness are also lower compared to girls (Mäkipää et al, 2021b), which might suggest that boys are unable to use teacher feedback efficiently. Due to their lesser results and levels of metacognitive awareness, it is probable that boys' learning to learn skills are inferior to those of girls, which is why teachers provide boys with more feedback.…”
Section: Implications Of the Resultsmentioning
confidence: 99%
“…A Likert scale from one to five (I completely disagree -I completely agree) was used in the closed-ended questions. In the quantitative analyses, gender and previous course grades were used as independent variables because research has found differences between boys and girls in grades (Kupiainen et al, 2018), metacognitive awareness (Mäkipää et al, 2021b), and perceptions of feedback in terms of proficiency (Guo & Barrot, 2019;Mäkipää, 2021;Tarnanen & Huhta, 2011;Zhang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Empirical studies have focused on the interactions between metacognitive awareness and other variables. For instance, learning achievements and performance are the influential factors that were given a significant amount of attention, such as the impact of metacognitive awareness on learning achievement for specific subjects (e.g., Mathematics learning; Bulut, 2021 ; foreign language learning; Mäkipää et al, 2021 ), for disparate groups of learners (e.g., undergraduate students; Pradhan and Das, 2021 ; secondary school students; Jaleel, 2016 ), and the interplay between metacognitive awareness, learning achievement, and other psychological variables (e.g., emotions; Wang and MacIntyre, 2021 ; motivation; Cakir and Guven, 2019 ). In light of the influence of metacognitive awareness on learning achievement, researchers have also been evaluating potential ways to promote learners’ metacognitive awareness, such as problem-based learning ( Kuvac and Koc, 2019 ), online flipped classrooms model ( Khodaei et al, 2022 ), and collaborative intervention ( Sandi-Urena et al, 2011 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The Metacognitive Awareness Inventory (MAI) developed by Schraw & Dennison (1994) usually measures learners’ metacognitive skills. It follows a common model of two components, i.e., Regulation of Cognition and Knowledge of Cognition ( Mäkipää, Kallio & Hotulainen, 2021 ). Regulation of Cognition expresses the students’ need to modify to students’ modifying the progress of their cognitive activity and control of their own cognitive processing ( Cleary & Kitsantas, 2017 ) while Knowledge of Cognition refers to what learners know about their own cognition or about cognition in general.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Regulation of Cognition expresses the students’ need to modify to students’ modifying the progress of their cognitive activity and control of their own cognitive processing ( Cleary & Kitsantas, 2017 ) while Knowledge of Cognition refers to what learners know about their own cognition or about cognition in general. It involves procedural, conditional, and declarative knowledge ( Mäkipää, Kallio & Hotulainen, 2021 ). In brief, interest in the metacognition role has been steadily rising in most education forms ( Meijer et al, 2013 ).…”
Section: Literature Reviewmentioning
confidence: 99%